Female Leadership and Institutional Support in Higher Education: Insights from KP (Pakistan) (Journal of Asian Development Studies, 2025)
Women's leadership in higher education remains an underexplored yet critical dimension of institutional development in Pakistan. While women now represent a significant share of students and faculty, their presence in senior leadership positions remains disproportionately low. This study examines the experiences of ten female leaders in universities across Khyber Pakhtunkhwa (KP), highlighting the structural, cultural, and interpersonal challenges that shape their leadership trajectories. Guided by the role congruity theory of prejudice toward female leaders, the research employed a qualitative design, drawing on in-depth interviews to capture women's lived realities. Findings reveal recurring barriers, including blocked promotions, frequent departmental transfers, exclusion from decision-making, and hostile behaviour from junior colleagues. Participants described institutional practices that destabilised their leadership authority, such as being repeatedly shifted after setting up departments or having their promotion cases delayed when higher roles were anticipated. Cultural norms and organisational politics intersect to reinforce gendered power dynamics, often leaving women isolated and without adequate administrative support. Despite these challenges, participants demonstrated resilience, continuing to perform leadership duties and advocate for inclusive practices. Comparative analysis across other provinces and global contexts suggests that, while the nature of gender bias varies, the systemic exclusion of women from leadership is a shared concern. The study underscores the urgent need for institutional reforms, including transparent promotion criteria, stable appointments, mentoring systems, and gender-sensitive governance structures. Addressing these gaps will not only enhance women's participation in leadership but also strengthen the inclusivity and effectiveness of higher education in KP.